1989
DOI: 10.4315/0362-028x-52.10.733
|View full text |Cite
|
Sign up to set email alerts
|

Natural Occurrence of Clostridium botulinum on Fresh Mushrooms (Agaricus bisporus)

Abstract: Clostridium botulinum was not found (<l/100g) in fresh commercial mushrooms produced in the Netherlands. The log10 mean number of anaerobic spores in mushrooms was 3.19/g. In casing soil of mushroom production beds, however, C. botulinum was detected, and numbers varied from <1.3 to 1.6/100 g. Log10 counts of anaerobic spores present in this material amounted to 5.58/g. If it is assumed that the ratio of the number of anaerobic spores to the number of C. botulinum in mushrooms is the same as that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Brown and Gaze (1990) used 10 1 -10 2 /g, which was close to the levels detected in foods -5.3 spores/g of type E spores in raw trout (ICMSF, 1996), for example. However, other authors (Notermans, Dufrenne, & Gerrits, 1989; reported the range of 0.04-1.6 spores/kg. Betts (1996) suggested a higher than natural concentration of spores for challenge studies, but warned against too high levels, which can upset the preservation system.…”
Section: General Considerationsmentioning
confidence: 92%
“…Brown and Gaze (1990) used 10 1 -10 2 /g, which was close to the levels detected in foods -5.3 spores/g of type E spores in raw trout (ICMSF, 1996), for example. However, other authors (Notermans, Dufrenne, & Gerrits, 1989; reported the range of 0.04-1.6 spores/kg. Betts (1996) suggested a higher than natural concentration of spores for challenge studies, but warned against too high levels, which can upset the preservation system.…”
Section: General Considerationsmentioning
confidence: 92%
“…They assumed that the ratio number of anaerobic spore formers to number of C. botulinum in mushrooms was the same as that detected in the casing soil, and thus these authors estimated that the incidence of C. botulinum in mushrooms was between <0.08 to 0.16 organisms per 100 g of product. The levels of C. botulinum in mushrooms estimated by Notermans et al (1989) were lower than those inoculated by Sugiyama and Yang (1975) and detectable botulinal toxin was not produced unless large numbers of C. botulinum spores were inoculated into mushrooms (Sugiyama and Yang 1975).…”
Section: Microbiologymentioning
confidence: 97%
“…Sugiyama and Yang (1975) 10 3 cfu g -1 of C. botulinum type A, packaged in non-perforated PVC at 20ºC, in which O 2 levels below 2% were reached. On other hand, Notermans et al (1989) found anaerobic spore formers counts between 2.7 and 3.7 log 10 cfu g -1 in mushrooms collected from production farms. These authors found C. botulinum in the casing soil but not in the mushrooms.…”
Section: Microbiologymentioning
confidence: 99%
“…This sporeformer anaerobic bacterium is naturally present in different environments such as soil, sediment of superficial water, fresh vegetables and spices. It can be isolated from different kinds of foods of animal and vegetable origin 5,9,10,15,23 . Four biological groups and eight types (A, B, C1, C2, D, E, F, and G) are recognized 5,9,10,17,23 , based on structural features, proteolytic activity and distinct antigenic toxins.…”
Section: Introductionmentioning
confidence: 99%
“…Types A, B, E and more rarely F, are related with human cases of botulism; type G may cause disease in primates, what indicates the possibility of affecting men 5,18,23 . Types A, B and F are mainly found in soils and the intestinal tract of terrestrial animals; type E is found in marine aquatic environment 5,9,11,13,15,21,22,23 . Four categories of botulism are recognized: classical or foodborne, due to ingestion of preformed toxin in foods; wound botulism due to production of toxin in vivo, in the infected wound; infant botulism due to C. botulinum colonization of the intestinal tract, in the absence of natural microbiota (children 3-6 months old) and undetermined botulism, involving persons in which no food or wound source is detected, and that may be also related with colonization of the intestines 2 .…”
Section: Introductionmentioning
confidence: 99%